The first case of septic arthritis of the knee caused by Eggerthia catenaformis. (February 2022) - Sreckovic, Svetlana; Kadija, Marko; Ladjevic, Nebojsa; Starcevic, Branislav; Stijak, Lazar; Milovanovic, Darko
Abstract: Eggerthia catenaformis has been reported as a human pathogen. We present the first case of the primary knee infection caused by Eggerthia catenaformis in a 23-year-old male patient with a knee infection, after primary anterior cruciate ligament reconstruction. Eggerthia catenaformis was confirmed by MALDI-TOF mass spectrometry from synovial fluid. The dental focus was excluded. The isolated bacterial strain showed sensitivity to all of the tested antimicrobials. However, for successful management of knee infection, besides culture-directed antibiotics therapy, arthroscopic debridement and lavage were necessary. Highlights: Eggerthia catenaformis has been rarely reported as a human pathogen. Eggerthia catenaformis should be considered as a cause of septic arthritis. Eggerthia catenaformis should be confirmed by mass spectrometry. Antibiotics are not enough for the successful treatment of knee infection. Besides antibiotics, the arthroscopic debridement and lavage are of key importance.